Multi-stakeholder platforms for value chain analysis and upgrading. The case of Cocoa in the Colombian Northern Amazon - Charry, Andres; Jäger, Matthias; Hurtado Bermudez, Jhon Jairo (International Center for Tropical Agriculture, 2017)
The Colombian government is implementing a post conflict agenda that includes rural reforms, focused on areas previously under the FARC guerrilla’s control. Simultaneously and connectedly, the country is experiencing increasing rates of deforestation. To align efforts against deforestation and the promotion of new development models for the Amazon Region, the Ministry of Environment and Sustainable Development created a program called Visión Amazonía (VA). One of VA components includes the strengthening of agricultural value chains (VCs) committed to zero deforestation goals (MADS, 2015) through the collective construction of upgrading strategies. The cocoa VC has been prioritized given its reforestation capacity, suitability to local conditions, market potential and the existence of committed producer organizations in the region. The International Center of Tropical Agriculture (CIAT) facilitated the consolidation of multi-stakeholder platforms for developing the sector´s VC upgrading strategy in the departments of Guaviare and Caquetá, by using a participatory process that involves key stakeholders along the entire VC.